MANAJEMEN TENAGA PENDIDIK DAN KEPENDIDIKAN DI SEKOLAH DASAR ISLAM - Nadjematul Faizah (STIT AL-AMIN KREO TANGERANG, 2023)
The research objective is to describe the management of teaching and educational staff in educational institutions, especially Islamic schools. Qualitative research methods through case study studies. Data collection techniques: interviews with 1 school principal, 3 teachers and 1 administrative staff and 1 security guard; run and observation. Data analysis techniques: reduction, data presentation and conclusion. Data validation technique with technique and source triangulation. Research results: (1) planning: first quantity analysis: determining the amount according to the needs of the school. Two payment criteria: Islamic religion, at least being able to read the Koran, Muslim clothing (covering the genitals), linear diploma, able to work individually and in groups. (2) procurement: job vacancies and cooperation with other schools. (3) coaching and development: further studies, training/seminars/workshops and regular meetings, monthly religious coaching. (4) promotions and transfers: promotions and workplace transfers. (5) dismissal: severe prohibition, death and age. (6) compensation and awards: salary, benefits, trophies/certificates, further studies, umrah, pilgrimage